New records of the oak lace bug Corythucha arcuata (Say, 1832), brown marmorated stink bug Halyomorpha halys (Stål, 1855), and western conifer seed bug Leptoglossus occidentalis Heidemann, 1910 in Ukraine - Grigoriy Dragan (Інтродукція Рослин)
The paper reports the finding of three invasive species of bugs: Corythucha arcuata (Say, 1832), Halyomorpha halys (Stål, 1855), and Leptoglossus occidentalis Heidemann, 1910 in the plantations of the dendrological park “Olexandria” and the adjacent territory. For the first time, a hotspot of C. arcuata mass reproduction in oak plantations in the Kyiv region was reported. The significance of these findings for park ecosystems is briefly discussed.